Валеологические методы адаптации студентов университетов к учебному процессу - Коновалова, Е.О.; Гончаренко, А.В.; Лойко, Л.С. (Харкiвський нацiональний унiверситет iм. В.Н. Каразiна, 2008)
Состояние здоровья студентов оценивалось в весеннем семестре 2008 г: до и после приема таких продуктов оздоровительного питания, как фиточай «Веснянка», фитосироп «Валеотон», блюда из проростков зерновых культур. Показано, что наибольшее положительное влияние на изучавшиеся показатели оказал фитосироп, который может быть рекомендован для оздоровления студентов в периоды наибольшей учебной нагрузки. Фиточай лучше пить в начале семестра или после курса оздоровления сиропом для сохранения достигнутого уровня здоровья. Блюда из проростков необходимо внедрять в ежедневный рацион студентов для достижения стабильного оздоровительного эффекта. Стан здоров'я студентів оцінювався у весняному семестрі 2008 г: до і після прийому таких продуктів оздоровчого харчування, як фіточай «Веснянка», фітосироп «Валеотон», блюда з паростків зернових культур. Показано, що найбільший позитивний вплив на показники, що вивчалися, мав фітосироп, який може бути рекомендований для оздоровлення студентів у періоди найбільшого навчального навантаження. Фіточай краще пити на початку семестру або після курсу оздоровлення сиропом для збереження досягнутого рівня здоров'я. Блюда з паростків необхідно впроваджувати до щоденного раціону студентів для досягнення стабільного оздоровчого ефекту. The state of health of students of university was estimated in a lent term 2008. To the students 1, 2, 3 courses such health food stuffs as phytotea «Vesnyanka», phytosyrup «Valeoton», dishes from sprouts of grain-growing, cultures accordingly. Thus, as a result of definition of level of physical health, functionality of an organism and adaptic possibilities of cardiovascular system at students of 1st course before tea reception «Vesnyanka», at students of 2nd course before syrup reception «Valeoton» and the uses in nutrition of sprouts students of 3rd course it is shown, that the greatest positive influence on studied indicators was rendered by a phytosyrup which can be recommended for improvement of students during the periods of the greatest academic load. Phytotea is better for drinking in the beginning of a semester or after a course of improvement by a syrup for conservation of the reached level of health. Dishes from sprouts are necessary for introducing in a daily ration of students for achievement of stable improving effect.
Keywords: здоровье студентов; кардиореспираторная система; фитосироп; фиточай